Synthesis, Characterization and Study of the Effect of Nanoparticles on the Biological Activity of New Silicon Polymers and Their Nanocomposites - Ahmed, Basma J.; Naif, Thikra A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
A new class of silicone polymers was synthesized based on dichlorodi(methyl)silane (DCDMS) with some organic compounds [M1-M6] containing terminal hydroxyl groups previously synthesized by different chemical reactions, and their nanocomposites were synthesized using silver nanoparticles (Ag-NPs). All polymers were synthesized using condensation polymerization and characterized by FTIR and 1HNMR spectra. The biological activity of silicone polymer P5 was evaluated using different weights of silver nanoparticles (1%, 3%, 5%, and 7%) against Escherichia coli (Gram-negative) and Staphylococcus aureus (Gram-positive). The results showed that the higher the percentage of silver nanoparticles, up to 7%, the higher the biological activity, and accordingly, this percentage of silver nanoparticles was used to synthesize and measure the biological activity of nanocomposites P1-P5 and P6 against the same two types of bacteria. The nanocomposites showed antibacterial activities against Escherichia coli (Gram-negative) and against Staphylococcus aureus (Gram-positive) better than silicon polymers without silver nanoparticles (Ag-NPs). The results also showed that P6 was more antibacterial when pure than the other polymers. The polymer P’4 with silver nanoparticles (7%) was 20 times more antibacterial against Escherichia coli and 25 times more antibacterial against Staphylococcus aureus. This means that P’4 has more antibacterial activity against the same two types of bacteria than other nanocomposites.